Customer Loyalty Analysis in PT. BNI-46 (Persero) Support Branch of Graha Pangeran Surabaya - Apria Tika Dewi; Dhani Ichsanuddin Nur (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
BANK is a financial institution that plays an important role in the economy which influences the movement of economic growth with the aim of improving the standard of living of the people at large. Based on the background of the problem, regarding the provision of good service quality to customers and the satisfaction received by customers with bank trust are the reasons for customers in choosing a bank so that customer loyalty can be created. This study aims: to determine the effect of trust on customer loyalty, to determine the effect of service quality on customer loyalty, to determine the effect of trust on customer loyalty through customer satisfaction and to determine the effect of service quality on customer loyalty through customer satisfaction.The main method of this research is to emphasize objectively measuring aspects of social phenomena. Based on the objective, the method used is quantitative research. The population in this study were all customers of PT. BNI 46 Graha Pangeran Surabaya Sub-Branches totaling 16,071 customers using a sampling technique so that in this study the number of research samples was determined as many as 99 customers. The analysis technique used is Data Analysis Using Partial Least Square (PLS).The results showed that customer trust can contribute to increasing customer satisfaction, service quality has not been able to contribute to customer satisfaction, customer trust can contribute to increasing customer loyalty, service quality has not been able to contribute to customer loyalty, customer satisfaction can contribute to customer loyalty. increasing customer loyalty and customer trust can contribute to increasing customer loyalty through customer satisfaction and service quality has not been able to contribute to customer loyalty through customer satisfaction.